2000
DOI: 10.1046/j.1365-2559.2000.00882.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytokeratin 5/6 immunohistochemistry assists the differential diagnosis of atypical proliferations of the breast

Abstract: Immunophenotyping of keratin 5/6 expression can be helpful in the diagnosis of atypical hyperplasias and in-situ carcinomas of the breast. It is particularly valuable in the differential diagnosis between benign and atypical proliferative lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
150
0
4

Year Published

2002
2002
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(167 citation statements)
references
References 30 publications
12
150
0
4
Order By: Relevance
“…[5][6][7] In addition to routine hematoxylin and eosin-stained sections, various immunohistochemical markers have been used to aid in the distinction between such intraductal epithelial proliferations. Of these, high-molecular weight cytokeratins (CKs) traditionally expressed by the basal epithelial/myoepithelial cells of normal breast, including those detected by the 34bE12 antibody (CK1, CK5, CK10 and CK14) and CK6, have been useful in evaluating both nonpapillary [8][9][10][11] and papillary [12][13][14][15] lesions. In general, these studies have found greater expression of high-molecular weight CKs in usual ductal hyperplasia compared with atypical ductal hyperplasia and ductal carcinoma in-situ, and in intraductal papillomas compared with papillary carcinomas.…”
mentioning
confidence: 99%
“…[5][6][7] In addition to routine hematoxylin and eosin-stained sections, various immunohistochemical markers have been used to aid in the distinction between such intraductal epithelial proliferations. Of these, high-molecular weight cytokeratins (CKs) traditionally expressed by the basal epithelial/myoepithelial cells of normal breast, including those detected by the 34bE12 antibody (CK1, CK5, CK10 and CK14) and CK6, have been useful in evaluating both nonpapillary [8][9][10][11] and papillary [12][13][14][15] lesions. In general, these studies have found greater expression of high-molecular weight CKs in usual ductal hyperplasia compared with atypical ductal hyperplasia and ductal carcinoma in-situ, and in intraductal papillomas compared with papillary carcinomas.…”
mentioning
confidence: 99%
“…2,8,11,12 Basal phenotype tumors represent a histologically poorly differentiated estrogen receptor (ER)-negative tumor subtype. 4,6,7,9,10,[13][14][15][16] The precise prevalence and clinicopathological characteristics of basal and luminal CK-expressing and -coexpressing tumors remain unclear. In particular, it is currently not known whether amplification of the HER-2 oncogene is characteristic of basal or luminal phenotype tumors, or whether there is no association.…”
mentioning
confidence: 99%
“…These features are highlighted by the use of high-molecular weight cytokeratins like 34bE12, CK5/6 and CK14. 25,29,30 With the use of this combination of high-and low-molecular weight cytokeratin antibodies along with the H&E slides, we observed significant improvement in the concordance rate among pathologists from fair (0.34 of stage 1) to moderate (0.50 of stage 3). Similar to our study, Douglas-Jones et al 31 have reported an improvement in the diagnostic agreement of core biopsy specimens with the use of immunohistochemistry for CK5/6, calponin and p63.…”
Section: Discussionmentioning
confidence: 81%